'Robin of Redesdale's Rebellion' of 1469. (3rd July 2021) - Tucker, Penny
Abstract : The defeat in July 1469 of forces loyal to the king, Edward IV, by an army of Yorkshire rebels led by someone who called himself Robin of Redesdale produced a second outbreak of civil war less than a decade after the first had brought King Edward to the throne and in due course almost unseating him. Although several historians have seen a connection between this rebellion and a slightly earlier one, which reportedly occurred in the north and was also led by someone known as Robin of Redesdale, it remains unclear what relationship if any there was between the two Robin of Redesdale rebellions and other northern uprisings in the spring and summer of 1469. One aim of this article is to answer that question and to try to establish what really happened. Much more importantly, it aims to shed light on the nature of the original plan, why the July uprising when and in the form that it did, and why it had such disastrous consequences.